Bandits and Partisans : The Antonov Movement in the Russian Civil War - Landis, Erik C. (Book collections on Project MUSE., 2008)
"Beginning in the fall of 1920, Aleksandr Antonov led an insurgency that became the largest armed peasant revolt against the Soviets during the civil war. Yet by the summer of 1921, the revolt had been crushed, and popular support for the movement had all but disappeared. Erik Landis mines recently opened provincial and central Soviet archives and international collections to provide a depth of detail and historical analysis never before possible in this definitive account of the uprising."